International experience in the field of employment of persons with disabilities - Babich, Oleksandr (Theory and Practice of Public Administration, 2024)
The article uses a method of generalization to determine the forms of support and employment of people with disabilities that can be used in Ukraine, in particular, in the employment of persons who received a disability as a result of military operations on the territory of the state. Determining the forms of employment used in the advanced countries of the world, it can be argued that their list cannot be exhaustive, as they are able to change based on the capabilities of authorities and institutions of civil society, the needs of employers and persons with disabilities.The article proves that for the employment of persons with disabilities, it is advisable for institutions that make a conclusion about a person’s partial fitness for work to provide recommendations regarding one or another type of activity in their conclusions. The recommended type of activity should be one that does not limit a person’s abilities. The simultaneous presence of different types of violations among people with disabilities is becoming more and more common with the beginning of the Russian attack on Ukraine, especially after the full-scale invasion, so the recommendations of the relevant institutions can be the primary help in further employment of people with disabilities.In the article, based on the analysis, it is concluded that in Ukraine there are significant differences in the realities of employment of people with disabilities compared to EU countries, which means significant impoverishment for the majority of such people. For Ukraine, the impoverishment indicator for this category of persons is not calculated, besides, the methods of assessing the level of poverty in our state and EU countries are quite different. In our country, despite the fairly socially oriented legislation regarding the employment of people with disabilities, its real provision remains significantly lower than in the countries of the European Union. The rate of employment of persons with disabilities for the leading EU countries and Ukraine differs by more than four times, which requires the authorities of our country to implement advanced European practices.